O SILENCIAMENTO DA PERSPECTIVA BIOPSICOSSOCIAL DE INCAPACIDADE: uma análise arqueológica do discurso jurídico - DAMASCENO, Gioliano Antunes (2016)
The legal concept of incapacity for grant the welfare benefit of continuing provision for people with deficiency (BPC) has undergone significant change from 2011, when the Organic Law of Social Assistance (LOAS) endorsed the importance of the elements "extra-disease" - that is, those that do not concern the clinical context, but the social environment in which the subject is inserted - as determining factors for the establishment of incapacity. In this thesis, the purpose is to analyze how the fact that the expertise have been conducted exclusively by doctors and the dominance of the discourse of managerial administration in the Brazilian judiciary took, on 10 cases selected to research, to break with this biopsychosocial perspective of incapacity provided for in LOAS, giving rise, in medical reports and court decisions, to a strictly biomedical discourse. The theoretical framework has bases in Michel Foucault's ideas, especially those of your call "archaeological phase". It is conceived, in this sense, the break in question as a discursive discontinuity and makes up a reading their respective causes, outlined above, in the light of Foucault categories "formation rules" and "positivity system”.